Effect of Transformational Leadership Style on Job Satisfaction of University Teachers - Sabiha Bibi; Dr. Wajiha Kanwal; Khalida Parveen (Journal of Management Practices, Humanities and Social Sciences, 2022)
Leadership style is the general way a leader behaves towards his subordinates for attaining objectives. Leadership styles play very important role in the success of an organization. Objectives of the study were (i) To find out the level of transformational leadership style of head of the departments. (ii) To identify the level of job satisfaction of university teachers. (iii) To find out the effect of transformational leadership style of department heads on job satisfaction of teachers. As the nature of the research was quantitative, survey method was used for investigating about effect of transformational leadership style on job satisfaction of university teachers. Multifactor Leadership Questionnaire and Minnesota Satisfaction Questionnaire were used. The population of the study comprised of teaching faculty of public and private universities in Islamabad Pakistan. By using convenient sampling technique 150 teachers were selected from three universities. Thus, the aim of this study was to examine the effect of transformational leadership on job satisfaction of university teachers. The result showed there is a positive significant effect of Transformational leadership style on Job Satisfaction of university teachers. Moreover, the Idealized influence found a highest impact on Job satisfaction than other Transformational Leadership dimensions. Universities should pay more attention to Transformational Leadership and improve the leader's characteristics among university leaders to enhance the Job Satisfaction of university teachers.